Aspergillus rot of ripe mangoes ( Mangifera indica L.) var. Ambalavi, Willard and Karuthakolumban - Krishnapillai, N.; Vijayakumaran, W.R.S. (Journal of the National Science Foundation of Sri Lanka, 2012)
Karuthakolumban, Willard and Ambalavi are considered the desirable dessert mango varieties in Jaffna. These varieties are, in general, grown in home gardens. Postharvest losses of mangoes are high in Jaffna due to two major postharvest diseases, stem-end rot and anthracnose. However, in July 2009 approximately 10 % of the harvested mangoes var. Ambalavi from a home garden at Thirunelvely were observed with different symptoms light yellow colour suppressed lesions around the stemend region. The lesions increased in size resulting in depressed mesocarp and a soft rot condition. The centre of the lesion became sunken and was covered with brownish black spores. Isolated colonies of the causal organism on potato dextrose agar (PDA) were initially white in colour. Black colour conidia production was observed 36 hours after inoculation and was followed by the appearance of black colour colonies with a diameter of 8 cm, three days after inoculation. The reverse side of culture plates was off-white in colour with a fracture like appearance. The hyaline, septate mycelia with black colour conidia and the spore bearing structures are characteristics of Aspergillus niger (Bennett, 2010). ‘T’ shaped foot cells that produce a single conidiophore were observed. The size and arrangement of the conidial heads as well as the colour of the spores are important morphological Aspergillus. grown on PDA to the surface sterilized, wounded, mature Ambalavi mangoes. Non inoculated Ambalavi mangoes were kept as control. The control and the inoculated mangoes were kept were developed in the inoculated six days (Figure 1) while there was no rotting observed in the control fruits. Koch’s from inoculated fruits. The diseased mangoes were brought to the Post harvest Laboratory, Industrial Technology Institute, as A. niger (Figure 2) on the basis of cultural and morphological characteristics (Watanabe, 2002). A. niger decaying plant material and in a large number of foods and feeds all over the world (Perrone et al., 2007; Pitt & Hocking, 2009; Gautam et al., 2011). During April to August 2011, Aspergillus rot was recorded in the most popular dessert mango varieties in Jaffna, Karuthakolumban and Willard. It was thus concluded that Aspergillus rot is also an important postharvest problem in Jaffna with three years subsequent observations in markets and home gardens during 2009 to 2011. Based on morphological characters and as A. niger. Aspergillus rot caused by A. niger have been reported in other countries of the world (Prakash & Raoof, 1989;
Keywords: Aspergillus niger; mangoes